Differences Between Student’s Mathematical Problem Solving Ability and Learning Motivation Taught By Using Geogebra-Assisted Cooperative and Contextual Learning Model - Saragih, Doni Irawan; Minarni, Ani (Advances in Social Sciences Research Journal, 2018)
This research aimed to: (1) analyze the differences between student’s mathematical problem solving ability taught by using GeoGebra-assisted cooperative and contextual learning model; (2) analyze the differences between student’s learning motivation taught by using GeoGebra-assisted cooperative and contextual learning model; (3) analyze the process of student’s answer mathematical problem solving test that taught by using Geogebra-assisted cooperative and contextual learning model. The instruments used in this research consisted of: (1) mathematical problem solving ability test, (2) learning motivation questionnaire. The data was analyzed by using Two Way Anova. This result research showed that: (1) there are differences between student’s mathematical problem solving ability taught by using GeoGebra-assisted cooperative and contextual learning model, (2) there are differences between student’s learning motivation taught by using GeoGebra-assisted cooperative and contextual learning model, (3) the process of student’s answer taught by using contextual learning model is better than cooperative learning model.